Circularly Polarized Luminescence of Chiral Pt(pppb)Cl (pppbH=1‐pyridyl‐3‐(4, 5‐pinenopyridyl)benzene) Aggregate in the Excited State. Issue 2 (28th October 2015) - Tanaka, Saori; Sato, Kyohei; Ichida, Kyoko; Abe, Taichi; Tsubomura, Taro; Suzuki, Takayoshi; Shinozaki, Kazuteru
Abstract: We prepared enantiomers of chiral Pt II complexes, Pt(pppb)Cl and Pt(pppb)CN (pppbH=1‐pyridyl‐3‐(4, 5‐pinenopyridyl)benzene), and measured their CPL (circularly polarized luminescence) spectra for excimer and trimer emission. The contribution of the pinene moiety to CPL was considerably low for the π–π* emission of the monomer but large for MMLCT (metal‐metal‐to‐ligand charge‐transfer) of the excimer and trimer which had a helical structure induced in a face‐to‐face stacking fashion. The trimer CPL for (+)‐Pt(pppb)Cl was larger in intensity than that of excimer CPL; on the other hand, that for (+)‐Pt(pppb)CN was opposite in sign compared with that of excimer CPL. We conclude that differences in the excited‐state structure of the aggregate between Pt(pppb)Cl and Pt(pppb)CN account for the variation in the CPL spectra. By the aid of TD‐DFT calculations it was predicted that the dihedral angle θ (Cl‐Pt‐Pt‐Cl) was 50–60° or 110–140° for Pt(pppb)Cl aggregates and 160° for Pt(pppb)CN aggregates. Abstract : Circularly polarized luminescence (CPL) of chiral Pt II complexes which show monomer, dimer, and trimer emission was investigated. Although the CPL could not be detected for monomer emission, those for excimer and trimer emissions were clearly observed. The CPL spectra and DFT calculation predicted the helical structures of excited Pt II complex aggregates.